Trend of Japanese encephalitis in North India: evidence from thirty-eight acute encephalitis cases and appraisal of niceties - Shailendra K. Saxena; Niraj Mishra; Rakhi Saxena; Maneesh Singh; Asha Mathur (Journal of Infection in Developing Countries)
Background: In the year 2005, an epidemic of Japanese encephalitis (JE) occurred in the northern states of India. The present study was planned to reconfirm the circulation of JE in the area and to assess the trend of the disease to slow down the burden of JE. Methodology: Surveillance was conducted to identify patients with acute encephalitis. Blood and cerebrospinal fluid specimens from suspected cases underwent pathological, serological, and demographic investigations. Viral testing for evidence of Japanese encephalitis virus (JEV) infection was also performed, either by IgM capture ELISA/RT-PCR or both. To identify circulating JEV strains, RT-PCR, sequencing and phylogenetic analysis was performed. Based on clinical cases reported between 1992 and 2008, the trend of JE infection in the state was analyzed to examine the dynamics of infection. Results: Our investigations (n = 38) revealed that only 55.3% cases were positive for JE. Pathological examination revealed marked pleocytosis in CSF (90±76.9 cells/mm3), and peripheral leucocytosis (64.7±8.86% neutrophils) with mild anemia. Males were more susceptible than females with a ratio of 1.63:1 and significant gender difference (P